The Value of Islamic Religiosity in the Migration of Admiral Cheng Ho in Archipelago, Indonesia - Auza, Ara; Andary, Ria Wuri; Tamsil, Ilma Saakinah (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to explain the value of Islamic religiosity in Admiral Cheng Ho's migration to Nusantara, Indonesia. This research uses library research. The descriptive analysis method collects, compiles, analyzes, and draws conclusions. The results showed that China communicated Islamic culture as an effective way to be accepted in the archipelago. The migration step of Chinese diplomacy through Admiral Cheng Ho is said to have reflected the "Clean Diplomacy" diplomacy theory by emphasizing that diplomacy focuses not only on the ends but also on the means, and all negotiation processes are equally important. The value of religiosity in life practiced by Admiral Cheng Ho, believing in Allah SWT, appreciating, and respecting the people in the archipelago, illustrates the behavior of loyalty to the Chinese ruler by spreading Islam in the archipelago through trade routes.